Adsorption of pathogenic microorganisms, NH4+ and heavy metals from wastewater by clinoptilolite using bed laminar flow. (2nd January 2018) - Ferronato, Chiara; Vianello, Gilmo; Antisari, Livia Vittori
Abstract: The contamination of water bodies in urban areas is a serious problem, which may increase when wastewater is discharged without complete remediation. Due to their high adsorption capacity and ion-exchange properties, zeolites, such as clinoptilolite, can be used successfully to detoxify the wastewater before discharging it into the water body. In this study, experimental use of clinoptilolite is presented for water remediation. A static flow (A) and a laminar flow (B) method were applied in order to evaluate the efficiency of clinoptilolite for reducing different contaminants in the outflow wastewater of an old municipal treatment plant in Bologna District (Northern Italy). Mesocosm experiments were performed in order to achieve reduction of the microbial faecal indicators and of the excess nutrients and heavy metals in the effluent. During the experiments, pathogenic microorganisms, ammonium and heavy metals were reduced by as much as between 78 and 95% within 24 h, highlighting the great efficiency of this low-cost material for water remediation.